Somesthetic senses.[article]. - Hollins, Mark
This is a review of recent advances in our understanding of the sensory modalities of touch, temperature sensitivity, and pain. Most of nthe research described is psychophysical or perceptual in nature, but physiological and imaging studies are included when they sharpen issues or reveal underlying mechanisms. Coverage of touch research comprises the subjects of acuity, vibrotaction and texture perception, perception of location and movemnet, tactile attention, and cross-modal phenomena. For pain, the covered topics are central sensitization, pain-touch and pain-pain interactions, placebo effects, the role of attention and emotion in pain, and the genetics of pain. For touch, the topics are arranged roughly in order of increasing cognitive involvement, but such as ordering is not feasible for pain, where attitudes and expectations can substantially affect even the most :sensory" of judgments.
Keywords: Attention; Emotion; Pain; Pain modulation; Texture perception; Thermoreception; Touch